The encyclopedia of housing - Van Vliet--, Willem, 1952- (Thousand Oaks, Calif. : Sage, 1998)
'Need to know how housing is financed? What is Situ construction? Need to define home matching? This encyclopedia provides access to a wealth of information drawn from many disciplines. With more than 500 entries, from abandonment to zoning, these capsules go beyond merely providing definitions of housing topics: they describe, elaborate, and critically assess issues of relevance to a wide variety of readers. Appendixes that cover major federal legislation and list major organizations and journals accompany the entries'.--'Outstanding Reference Sources : the 1999 Selection of New Titles', American Libraries, May 1999. Comp. by the Reference Sources Committee, RUSA, ALA.
Includes bibliographical references and indexes.
Keywords: Housing -- Encyclopedias; Housing -- United States -- Encyclopedias